Peran Dinas Pendidikan Sidikalang Kabupaten Dairi Dalam Meningkatkan Kompetensi Guru Melalui Program Pelatihan - Mulkan Sohniat Lingga; Rudi Salam Sinaga; Beltahmamero Simamora (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to evaluate the role of the Sidikalang Education Office, Dairi Regency in improving teacher competence through training programs. Teacher competence that includes pedagogical, professional, social, and personality aspects is a key factor in the success of the learning process. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Informants consisted of Education Office officials, teacher participants in training, and school principals. The results of the study indicate that the Education Office plays a role in planning, implementing, and evaluating ongoing training. The training held has a positive impact on improving teacher pedagogical skills, learning quality, and professionalism. However, a number of obstacles were found such as limited access for teachers in remote areas, lack of motivation for some teachers, and training materials that are less relevant to field needs. Optimization efforts are made through the use of technology, collaboration with educational institutions, and practice-based approaches. This study recommends the need for a more flexible and contextual training system in order to be able to reach all teachers fairly and have a direct impact on the quality of education.